Performance comparison of 2D nickel phosphate nanoparticles prepared via sonochemical and microwave-assisted hydrothermal routes for supercapattery - Norshahirah, Mohamad Saidi *; Artiqah, Khairudin; Li, Lijie; Muhammad Amirul, Aizat Mohd Abdah *; Ong, Gerard; Tan, Yee Seng *; Mohammad, Khalid *; Khan, Fayaz; Muhammad Norhaffis, Mustafa *; Arshid, Numan * (Elsevier, 2023)
Metal phosphates are broadly applied in electrochemical energy storage applications because of their abundance in nature, cost-effectiveness, and excellent electrochemical performance. Herein, we compare the performance of nickel phosphate (Ni3(PO4)2) prepared through sonochemical and microwave-assisted hydrothermal reaction (MW) synthesis routes for supercapattery. These methods are efficient, rapid, and facile, yielding a high quantity of nanoparticles. Field Emission Scanning Electron Microscopy reveals that Ni3(PO4)2 nanoparticles synthesized via the MW method are smaller than those produced via the sonochemical method. X-ray diffraction analysis confirmed that the MW method, followed by calcination at 200 °C for 3 h (NiPO4-MWB sample), produces amorphous nanoparticles, providing more exposure to redox-active sites. This work demonstrates that the NiPO4-MWB sample exhibits the highest specific capacity of 256.54C g−1 at a current density of 1 A g−1 compared to its counterpart electrode prepared via the sonochemical. A device fabricated using NiPO4-MWB//activated carbon (AC) delivered an energy density of 10.33 Wh kg−1 at a power density of 750 W kg−1, retaining 99.42 % of its capacity after 5000 cycles. The notable capacity retention makes it an attractive candidate for supercapattery electrodes. These findings suggest that MW synthesis can be used for the rapid production of tailored nanoparticles for electrochemical energy storage applications.